Magneto-dielectric coupling in SmFeO3: A study on anomalous dielectric, conductivity, impedance at spin reorientation temperature. Issue 11 (1st August 2018) - Khan, Azam Ali; Satapathy, S.; Ahlawat, Anju; Deshmukh, Pratik; Karnal, A.K.
Abstract: The SmFeO3, a family member of rare earth orthoferrite, is a potential candidate for future industrial (spintronics) applications due to highest spin reorientation temperature (453-483 K) among other RFeO3 members. There are ambiguous reports on high permittivity behavior of SmFeO3 . In this report, the origin of high permittivity in SmFeO3 is attributed to microstructure rather than inherent material property of material. Ceramic pellets of SmFeO3 were prepared in two different routes i. e. solid-state route and nano-combustion synthesis route. The dielectric and conductivity properties of these pellets were studied as function of frequency as well as temperature. Impedance spectroscopy was used to study the dielectric and resistive behavior of SmFeO3 . The central findings of this work are; (i) the high dielectric constant of SmFeO3 is not an inherent material property instead strongly dependent on microstructure and preparation conditions and (ii) the anomalous behavior in dielectric, conductivity and impedance observed at spin reorientation temperature regime of SmFeO3 is attributed to strong magneto dielectric coupling in SmFeO3 .